Where we live Level 1 Book 2 - Snowball, Dr. Lesley Fern, 2024; Dr. Lesley Fern Snowball 2024 (Pakistan Paramount Books, 2024)
The Paramount Happy Readers series is designed to help young learners develop early reading skills through engaging and level-appropriate stories. Each book introduces children to simple plots that are relatable and easy to understand. Through colorful illustrations, repetitive language, and interactive comprehension tasks, children gradually build vocabulary, fluency, and reading confidence. The stories often end with a gentle lesson or moral, promoting both literacy and character development.
Age-appropriate illustrations Gradual vocabulary building Sight words and phonics integration Simple sentence structures for early readers Follow-up comprehension questions and activities Moral lessons or key themes highlighted
M5
Emergent to Fluent (KG to Grade 5) Skill Focus: Vocabulary acquisition Sentence structure recognition Moral and social understanding Listening and speaking (for read-aloud use) Best Used For: Guided reading and shared reading Phonics and sight word practice ESL/EFL learners (due to controlled vocabulary) Home reading and reinforcement
Keywords: Supplementary reading material